Prospects and threats for developing organic agriculture: The example of Azerbaijan - Aliyev, Shafa Tiflis; Mammadova, Elnura Bunyad; Hamidova, Lala Adil; Dunyamaliyeva, Vafa Rashid; Hurshudov, Shahin Nadir (Journal of Eastern European and Central Asian Research (JEECAR), 2022)
The article’s purpose is to evaluate empirical evidence of the main threats to organic agriculture formation and provide the argumentation of its development prospects in Azerbaijan’s current conditions. Questioning of agricultural business owners identified threats and prospects for developing organic agriculture in Azerbaijan. The opportunities and threats for developing organic agriculture are determined and differentiated by groups of entrepreneurs doing business in traditional/organic agriculture. Based on the results of the clustering of the agricultural enterprises depending on the level, the priority of threats, and prospects for development, the strategies for developing organic agriculture in Azerbaijan have been determined: educational strategy of financial accessibility, innovative growth, and infrastructure development.